Lower Extremity Combat Sustained Peripheral Nerve Injury in US Military Personnel. Issue 3 (March 2021) - Eckhoff, Michael D.; Craft, Madison R.; Nicholson, Tyler C.; Nesti, Leon J.; Dunn, John C.
Abstract : Background: Since the civil war, combat sustained peripheral nerve injuries (CSPNI) have been documented during wartime. Warfare has evolved and current combat involves a greater severity of blast injuries secondary to increased use of improvised explosive devices. The purpose of this study was to describe CSPNI and report outcomes after evaluation and treatment. We hypothesize that a shorter time to evaluation will improve outcomes. Methods: A database including all active duty service members who sustained a CSPNI and were treated by the PNC between 2004 and 2009 was used. Service member demographic information, injury mechanism, CSPNI description, and Medical Research Council (MRC) final motor and sensory outcomes were queried from this database. Results: One hundred and four military service members sustained 144 PNIs. The average age was 26.7 years, and nearly all were men (98.1%). There was no correlation between Sunderland classification and age, specific PNI, injury type, or time to evaluation. Higher Sunderland classifications were found to be correlated with worse final motor (r = 0.51, P < 0.001) and final sensory (r = 0.41, P < 0.001) scores. Final motor and sensory scores were not associated with specific nerve injury, mechanism of injury, initial EMG, or surgical procedure. Shorter time to initial assessment was associated with improved final motor and sensory scores, but was not found to be statistically significant. Conclusions: As the complexity of CSPNIs progress as combat weaponry evolves, a firm understanding of treatment factors is important. Our study demonstrates in recent conflict that military service members' initial injury severity is a key factor in expected outcome.